Considerations on familial mediterranean fever (Research, Society and Development, 2023)
Introduction: Familial Mediterranean Fever (FMF) belongs to the group of autoinflammatory diseases, a class that is characterized by the dysregulation of the innate immune system, causing a characteristic clinical picture. Objective: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of familial Mediterranean fever, building knowledge based on case reports and consolidated scientific evidence. Materials and Methods: This is an integrative literature review on the general clinical characteristics of familial Mediterranean fever. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Mediterranean Fever"; "Familial Fever"; "Pathophysiology" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies show that FMF involves specific nuances within medicine, including historical, pathophysiological, clinical, epidemiological and therapeutic aspects. Conclusion: Autoinflammatory diseases are recently described entities and among them is FMF, a condition that is caused by mutations in the MEFV gene, which are responsible for a characteristic picture of fever, serositis and skin lesions similar to erysipelas, in association with other findings. This pathology requires continuous treatment, as well as the structuring of a therapy that covers acute crises and prevents progression to unfavorable prognoses.